Analisis Perbaikan Kualitas Pelayanan Jasa Penyewaan Gudang Menggunakan Metode Service Quality dan Importance Performance Analysis - Saidatuningtyas, Ifa; Rizal, Muhammad Alde (Politeknik ATI Padang, 2024)
Service quality is crucial for companies in the service sector, directly impacting customer satisfaction. PT BLI, a company offering TPS warehouse rental services, is facing issues with a low influx of containers and customer complaints. This research aims to analyze the service quality at PT BLI's warehouse storage section using the Servqual method, which encompasses five quality dimensions and 24 attributes, followed by Importance Performance Analysis (IPA) to identify attributes that require immediate improvement. The Servqual analysis revealed that 10 attributes of PT BLI's service quality do not meet customer expectations. Through IPA, five attributes were identified as high-priority for improvement: the safety of goods in the warehouse (gap of -0.07), the informativeness of employee service regarding activity updates (gap of -0.14), the speed of employees in processing goods in and out of the LCL warehouse (gap of -0.34), the ability of employees to understand consumer needs (gap of -0.01), and the communication skills of employees in providing excellent service (gap of 0.32). Addressing these critical service quality gaps will help PT BLI enhance customer satisfaction, reduce complaints, and potentially increase the number of incoming containers, positively impacting the company's standing in the warehouse rental industry.